Correction: Magnetic mesoporous bioactive glass for synergetic use in bone regeneration, hyperthermia treatment, and controlled drug delivery. Issue 41 (25th June 2020) - Ur Rahman, Muhammad Saif; Tahir, Muhammad Asif; Noreen, Saima; Yasir, Muhammad; Ahmad, Ijaz; Khan, Muhammad Bilal; Ali, Khawaja Waqar; Shoaib, Muhammad; Bahadur, Ali; Iqbal, Shahid
Abstract : Correction for 'Magnetic mesoporous bioactive glass for synergetic use in bone regeneration, hyperthermia treatment, and controlled drug delivery' by Muhammad Saif Ur Rahman et al., RSC Adv., 2020, 10, 21413–21419, DOI: ; 10.1039/C9RA09349D .